2018
DOI: 10.1002/cssc.201801898
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface‐Related Phenomena on Mechanism, Selectivity, and Conversion of TiO2‐Induced Photocatalytic Reactions

Abstract: Heterogeneous photocatalysis is the result of an inextricable connection of several factors differently contributing to the overall process. Photon absorption is the “sine qua non” condition for the reaction to occur. In fact, photons can be considered as immaterial reactants, and all of the phenomena related to the interaction of light–matter play a prominent role. However, other factors contribute in a concerted way to address the reaction, so that the relative contribution of each of them is often difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 107 publications
(133 reference statements)
0
16
0
Order By: Relevance
“…Considering the PC process in TiO 2 , the VB and CB level of TiO 2 lies at +2.9 and −0.3 eV, respectively, which leads to the band gap energy of 3.2 eV. It should be noted that the VB and CB level of TiO 2 lies at more positive and more negative values in comparison with the standard redox potential of O 2 /H 2 O (1.23 eV) and H+/H 2 (0 eV) vs. normal hydrogen electrode (NHE), which is one of the more favorable conditions for the photocatalytic redox reactions [31,32].…”
Section: Mechanics Of Tio 2 Photocatalysismentioning
confidence: 99%
“…Considering the PC process in TiO 2 , the VB and CB level of TiO 2 lies at +2.9 and −0.3 eV, respectively, which leads to the band gap energy of 3.2 eV. It should be noted that the VB and CB level of TiO 2 lies at more positive and more negative values in comparison with the standard redox potential of O 2 /H 2 O (1.23 eV) and H+/H 2 (0 eV) vs. normal hydrogen electrode (NHE), which is one of the more favorable conditions for the photocatalytic redox reactions [31,32].…”
Section: Mechanics Of Tio 2 Photocatalysismentioning
confidence: 99%
“…[97], copyright (2020) with permission from ACS publications) and (b) the z-scheme based heterojunction of core-shell CeO2@NiAl-LDHs (reprinted from [99], copyright (2021) with permission from Elsevier). The reaction has been investigated in irradiated aqueous suspensions of TiO 2 , one of the most extensively investigated photocatalysts, and the commonly accepted mechanism is the result of a photo-redox and β-scission pathway [104] Upon irradiation of suitable energy, electrons (e − CB ) and holes (h + VB ) are localized respectively within the conduction and valence band of TiO 2 [105], according to Equation (2).…”
Section: Other Photocatalystsmentioning
confidence: 99%
“…Yao et al [26] reported the enhanced visible light photocatalytic activity of Ag 3 PO 4 nanoparticles deposited onto commercial TiO 2 (Evonik P25). In this case, degradation of dyes such as methylene blue and rhodamine B have been used as model visible light reactions, so that it is difficult to assess if a direct or indirect photocatalytic process is taking place [27]. However, results were confirmed by Rawal et al [28], which used a homemade polycrystalline TiO 2 coupled with Ag 3 PO 4 for the visible light degradation of 2-propanol in gas phase.…”
Section: Introductionmentioning
confidence: 99%